1988
DOI: 10.1111/j.1545-5300.1988.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Lesbian and Heterosexual Couples on the Circumplex Model: An Initial Investigation

Abstract: This study extends the research on the Circumplex Model to a population of lesbian couples. Instruments consisted of a demographic questionnaire, FACES III, and the Family Satisfaction Scale. Lesbian couples reported significantly higher levels of cohesion, adaptability, and satisfaction than did heterosexual couples. Exceptionally high levels of cohesion and adaptability may help lesbian couples function more successfully in a predominantly heterosexual world. Further, women's socialization may predispose fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 18 publications
3
39
1
2
Order By: Relevance
“…Peplau (1982) compared gay, lesbian, and heterosexual couples on dyadic attachment and personal autonomy and found that the groups were similar to each other except in the area of sexual exclusivity. Interestingly, higher emotional and recreational intimacy, but lower sexual intimacy, also has been found among lesbian compared to heterosexual couples (Zacks, Green, & Morrow, 1988). In Kurdek's (1994) study of gay male, lesbian, and heterosexual couples there were similarities in areas of conflict and frequency of conflicts.…”
Section: Abstract Couples Merger Relational Interconnectednessmentioning
confidence: 81%
“…Peplau (1982) compared gay, lesbian, and heterosexual couples on dyadic attachment and personal autonomy and found that the groups were similar to each other except in the area of sexual exclusivity. Interestingly, higher emotional and recreational intimacy, but lower sexual intimacy, also has been found among lesbian compared to heterosexual couples (Zacks, Green, & Morrow, 1988). In Kurdek's (1994) study of gay male, lesbian, and heterosexual couples there were similarities in areas of conflict and frequency of conflicts.…”
Section: Abstract Couples Merger Relational Interconnectednessmentioning
confidence: 81%
“…These coresearchers clearly and repeatedly related they were in the relationship because they wanted to be, not because they felt they had to be. Because few sanctions exist against ending a dysfunctional relationship, those that endure might be better functioning than their heterosexual counterparts (Zacks, Green, & Marrow, 1988). This high level of personal dedication to the relationship might support, in part, why the 10 couples within the current study described such successful and satisfying relationships.…”
Section: Protection Against Stressorsmentioning
confidence: 82%
“…In other words, lesbian women develop feelings of guilt and shame in response to anti-homosexual messages they receive from society and as a result, they minimize any sexual attraction or desire they feel toward other women. It has also been suggested that since women are socialized to be less sexual and less sexually assertive than men, in a relationship with two women, there is no initiation of sexual activity because of the lack of a male sex drive (Blumstein & Schwartz, 1983;Gordon, 2006;Iasenza, 2000;Loulan, 1988;Nichols, 2004;Peplau & Fingerhut, 2007;Zacks, Green, & Marrow, 1988). Reduced desire and reduced initiative were also identified as the most important causes of lesbian bed death in a sample of 30 lesbian women in long-term relationships (van Rosmalen-Nooijens et al, 2008).…”
Section: Sexual Variablesmentioning
confidence: 96%